2015
DOI: 10.18251/ijme.v17i2.900
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural peer mentoring: One approach to enhancing White faculty adjustment at Black colleges

Abstract: White faculty members at America’s Black colleges face numerous social obstacles. Exploring the experiences of White faculty members at four historically Black Colleges and universities (HBCUs) and their adjustment to a minority status assists the comprehension of issues surrounding this subgroup. Utilizing a phenomenological approach, narratives from twenty-seven White faculty members were analyzed to garner an understanding of their experiences at these colleges. Strategies to developing faculty peer-mentori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…To make matters more complex, HBCUs now face increasing white enrollment and faculty (Shorette & Arroyo, 2015), prompting unique considerations concerning future development. This remains especially pressing when recognizing that, racially, HBCUs’ power structure is an inversion of broader society’s (Louis, 2015). To ensure their survival, many rural HBCUs must market themselves not only to urban Black students, but to local, often low-income, first-generation white students (Butrymowicz, 2014).…”
Section: Hbcus Rurality and Contested Meaningmentioning
confidence: 99%
“…To make matters more complex, HBCUs now face increasing white enrollment and faculty (Shorette & Arroyo, 2015), prompting unique considerations concerning future development. This remains especially pressing when recognizing that, racially, HBCUs’ power structure is an inversion of broader society’s (Louis, 2015). To ensure their survival, many rural HBCUs must market themselves not only to urban Black students, but to local, often low-income, first-generation white students (Butrymowicz, 2014).…”
Section: Hbcus Rurality and Contested Meaningmentioning
confidence: 99%
“…From response b) The notion of culture in mentoring was investigated by Peifer et al (2016), who found out that in cross-cultural mentorship, mentors who are empathetic succeed in bringing out the mentees so they can overcome cultural differences and get the mentorship done. Louis (2015) concurred, stating that cross-cultural mentoring could benefit the mentoring profession.…”
Section: Category 6: Lack Of Mergingmentioning
confidence: 99%
“…The United States population is becoming more diverse and so is the opportunities for those wanting to be faculty members. Academic institutions mainly; Colleges and Universities often boast about their diversity at their institutions more than any other business in society, yet underrepresented minorities are lacking the mentoring needed to be successful (Louis, 2015). Mentoring is a specific type of relationship between a senior superior ranked employee (mentor) and a new entry level employee (mentee) (Humbred & Rouse, 2016).…”
Section: Introductionmentioning
confidence: 99%